THE IMPACT OF INTER-AGENCY COLLABORATION TOWARD BORDER SECURITY IN MALAYSIA - Noor Azmi Mohd Zainol; Muhammad Thomas Angom Abdullah; Ariffin Ismail; Khairul Nizam Taib; Zahimi Zainol Abidin; Mohd Haniff Sofian, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Since Malaysia's independence, several government agencies have been established to regulate border security, including the Malaysian Armed Forces, Royal Malaysian Police, Malaysian Maritime Enforcement Agency, Immigration Department of Malaysia, Eastern Sabah Security Command, Malaysian Border Control Agency, and other enforcement entities. However, the effectiveness of border security efforts has been hampered by issues such as inadequate coordination, overlapping authority, unconsolidated resource usage, and competitive asset procurement among these agencies. These challenges have been exacerbated by increasing non-traditional threats, such as human trafficking, smuggling, and illegal immigration, which pose significant risks to national security. Therefore, the aim of this research is to evaluate the impact of collaboration among agencies in protecting national interests and to examine the steps taken by Malaysia's government to preserve border security. This study found that when all these agencies cooperate to safeguard national borders, they become more effective and have a greater impact. Despite this, the level of collaboration remains moderate, with operations carried out according to each agency's area of responsibility, and still falling short of achieving a fully integrated joint concept.